Mildred Pierce: from the novel to the miniseries. A relevant and valid female character with total relevance today - Gago Gelado, Rocío; Herrero de la Fuente, Mercedes (Investigaciones Feministas (Feminist Research), 2021)
By analyzing the work Mildred Pierce in its three formats: novel (1941), film (1945) and series (2011), we entered the study of the main character, who after the crisis of 1929 separated from her husband, initiating a stage of professional and personal independence, far from the standards that society of that time imposed on women. To do this, among the objectives we propose to discern whether the characteristics of this character and the archetypes in which he could be framed are affected by the moment in which each of the works analyzed is carried out, to conclude, as certain feminist scholars do, that the adaptation to the cinema presents a more stereotyped approach, which seems to punish with its dramatic outcome the aspirations of the protagonist. We also investigate the transformation arc of Mildred Pierce and discovered a complex character, currently in force, who evolves in the three works considered and who, fundamentally based on two archetypes ("Mother / Queen" and "Creator"), exhibits a multifaceted personality, credible and that allows our empathy.